Solving Quadratic Fractional Programming Problem via Feasible Direction Development and Modified Simplex Method - Abdulrahim, Basiya K. (Sulaimani Journal for Pure and Applied Sciences, 2013)
In this paper, I have expanded, the given algorithms [11,12] in to Quadratic Fractional Programming Problem (QFPP), I have used two methods to solve the problem one of them is Modified Simplex Method and the other Feasible Direction Development. And, then a good results I have been obtained as compared the ways of solution of the two methods. The computer application of our algorithms has also been discussed by solving constructed numerical example using Matlab2011 version 7.12.0.635 (R2011a). Finally this paper ends up with some conclusions.
Keywords: QFPP; Modified Simplex Method; Feasible Direction Development